Measurement of External Radiation Dose Rate in Radiotherapy Area at dr. Saiful Anwar General Hospital Malang - Novita Roysida (Jurnal VOK@SINDO, 2016)
Application of nuclear technology is very useful, but it is very risky for human health and safety. Therefore, it is necessary to control the radiation for humans and the environment.Radiation dose measurement in radiotherapy unit is considered to be a critical factor for optimizing radiation protection to the healthcare practitioners, the patient and the public. This paper presents an overview of average radiation dose measurement in public area around radiotherapy units at dr. Saiful Anwar General Hospital Malang. The recomendation of critical radiation dose from BAPETEN is bellow 50 mSv/ year for radiographer and bellow 5 mSv/year for public area. The measurement of radiation dose has been done around radiotherapy units (Co-60 teletherapy and brachiterapy) using RGD 20791 surveymeter.